Defining interdisciplinarity and indentifying Research directions in Jani Christou’s Strychnine lady - Yerosimou, Maria (Journal of Education Culture and Society, 2020)
Jani Christou was a major Greek composer, whose unusual, yet promising career was brought to an end after his untimely death in 1970 at the age of 44. His challenging and speculative output has intrigued generation of young music scholars; however, J. Christou’s work remains imperfectly and only patchily known and understood, especially outside Greece. This is partly because of the interdisciplinary nature of his late works which reduces the possibility of potential researchers who will academically establish J. Christou’s distinguished output. The aim of the present paper is to present and analyse parts of Strychnine Lady, a work composed in 1967 in order to propose research directions in an effort to confi rm J. Christou’s posthumous reputation.